Gemini lipopeptides as vaccine adjuvants: a new role for these versatile carriers - Grippo, Lucía Daniela (2020)
The design of subunit vaccines requires new adjuvant systems. We designed and synthesized new lipopeptides (cysteine-based) of low molecular weight with different hydrophobic chains that dimerize becoming gemini lipopeptides. They were characterized and their adjuvant capacity was tested in mice by the inoculation of a protein antigen formulated with the lipopeptides, with and without the addition of CpG-oligodeoxynucleotides. Formulations were able to induce an immune response and produced no adverse effects. An adjuvant ability is described for the first time for this type of molecules.